Banning goats could exacerbate deforestation of the Ecuadorian dry forest – How the effectiveness of conservation payments is influenced by productive use options - Santiago Ochoa M., W.; Paul, Carola; María Castro, Luz; Valle, Liz; Knoke, Thomas (ERDKUNDE, 2016)
Due to ongoing conversion of the dry forests of southern Ecuador to pasture and farmland, they are among the most threatened ecosystems globally. This study explored how to control deforestation in the region while securing the livelihoods of local people through land-use diversification and compensation payments. Results are based on interview data collected from 163 households near the Laipuna Reserve in southern Ecuador. Combining modern financial theory and von Thünen’s theory of land distribution, we optimized land-use shares of two types of forest management (banning and allowing goat grazing) and three crops (maize, beans and peanuts). Land-use portfolios were calculated for four different farm sizes, represented by the quartiles of the farm size distribution. We found that goat grazing was important for diversifying farm income and reducing financial risks for all farm sizes. However, forest area would still be converted to cropland under the current financial coefficients. The amount of compensation needed to maintain current forest cover was calculated for two different scenarios: 1) banning goat grazing and 2) allowing forest use where the farmer could decide how much forest area would be allocated to each land-use option. Offering financial compensation for forest preservation (Scenario 1) reduced deforestation but would still lead to a conversion of at least 23 % of current forests to croplands. Allowing forest use in a compensation scheme (Scenario 2) would help retain 96 % of the current forest cover, with 29 % of this forest being set aside for conservation. This scenario would suppose annual payments ranging from 4 to 89 ha-1, with the largest farms requiring the lowest payments. In contrast, banning goats from the forest would even risk losing the entire forest area to cropland, if compensation fell below 50 ha-1 yr-1. We conclude that coupling productive options with secure compensation payments and developing policies that support land-use diversification and sustainable use of forest resources, will be most effective in conserving the Ecuadorian dry forest.